A Hitchhiker's guide to Mediterranean marina travel for alien species. (1st July 2019) - Ulman, Aylin; Ferrario, Jasmine; Forcada, Aitor; Arvanitidis, Christos; Occhipinti-Ambrogi, Anna; Marchini, Agnese
Graphical abstract: Image 1 Highlights: Factors shaping non-indigenous species (NIS) richness are tested in the Mediterranean. There is a higher trend of NIS richness going from east to west in the Mediterranean. NIS richness in marinas is mainly influenced by proximity to other major vectors. NIS similarities between marinas are more influenced by environmental factors. The Suez Canal exerts a very strong influence for NIS in Mediterranean marinas.